Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2022)
Systemic lupus erythematosus (SLE) is a life-threatening autoimmune disease characterized by adaptive immune system activation, formation of double-stranded DNA autoantibodies and organ inflammation. Five patients with SLE (four women and one man) with a median (range) age of 22 (6) years, median (range) disease duration of 4 (8) years and active disease (median (range) SLE disease activity index Systemic Lupus Erythematosus Disease Activity Index: 16 (8)) refractory to several immunosuppressive drug treatments were enrolled in a compassionate-use chimeric antigen receptor (CAR) T cell program. Autologous T cells from patients with SLE were transduced with a lentiviral anti-CD19 CAR vector, expanded and reinfused at a dose of 1 × 106 CAR T cells per kg body weight into the patients after lymphodepletion with fludarabine and cyclophosphamide. CAR T cells expanded in vivo, led to deep depletion of B cells, improvement of clinical symptoms and normalization of laboratory parameters including seroconversion of anti-double-stranded DNA antibodies. Remission of SLE according to DORIS criteria was achieved in all five patients after 3 months and the median (range) Systemic Lupus Erythematosus Disease Activity Index score after 3 months was 0 (2). Drug-free remission was maintained during longer follow-up (median (range) of 8 (12) months after CAR T cell administration) and even after the reappearance of B cells, which was observed after a mean (±s.d.) of 110 ± 32 d after CAR T cell treatment. Reappearing B cells were naïve and showed non-class-switched B cell receptors. CAR T cell treatment was well tolerated with only mild cytokine-release syndrome. These data suggest that CD19 CAR T cell transfer is feasible, tolerable and highly effective in SLE.
CRIS-Team Scopus Importer:2022-09-30

Author Correction: Anti-CD19 CAR T cell therapy for refractory systemic lupus erythematosus. - Mackensen, Andreas; Müller, Fabian; Mougiakakos, Dimitrios; Böltz, Sebastian; Wilhelm, Artur; Aigner, Michael; Völkl, Simon; Simon, David; Kleyer, Arnd; Munoz, Luis Enrique; Kretschmann, Sascha; Kharboutli, Soraya; et al. (Nature Medicine, 2023)
EVALuna2:512812

CD19 CAR T-Cell Therapy in Autoimmune Disease - A Case Series with Follow-up. - Müller, Fabian; Taubmann, Jule; Bucci, Laura; Wilhelm, Artur; Bergmann, Christina; Völkl, Simon; Aigner, Michael; Rothe, Tobias; Minopoulou, Ioanna; Tur, Carlo; Knitza, Johannes; Kharboutli, Soraya; et al. (New England Journal of Medicine, 2024)
BACKGROUND: Treatment for autoimmune diseases such as systemic lupus erythematosus (SLE), idiopathic inflammatory myositis, and systemic sclerosis often involves long-term immune suppression. Resetting aberrant autoimmunity in these diseases through deep depletion of B cells is a potential strategy for achieving sustained drug-free remission. METHODS: We evaluated 15 patients with severe SLE (8 patients), idiopathic inflammatory myositis (3 patients), or systemic sclerosis (4 patients) who received a single infusion of CD19 chimeric antigen receptor (CAR) T cells after preconditioning with fludarabine and cyclophosphamide. Efficacy up to 2 years after CAR T-cell infusion was assessed by means of Definition of Remission in SLE (DORIS) remission criteria, American College of Rheumatology-European League against Rheumatism (ACR-EULAR) major clinical response, and the score on the European Scleroderma Trials and Research Group (EUSTAR) activity index (with higher scores indicating greater disease activity), among others. Safety variables, including cytokine release syndrome and infections, were recorded. RESULTS: The median follow-up was 15 months (range, 4 to 29). The mean (±SD) duration of B-cell aplasia was 112±47 days. All the patients with SLE had DORIS remission, all the patients with idiopathic inflammatory myositis had an ACR-EULAR major clinical response, and all the patients with systemic sclerosis had a decrease in the score on the EUSTAR activity index. Immunosuppressive therapy was completely stopped in all the patients. Grade 1 cytokine release syndrome occurred in 10 patients. One patient each had grade 2 cytokine release syndrome, grade 1 immune effector cell-associated neurotoxicity syndrome, and pneumonia that resulted in hospitalization. CONCLUSIONS: In this case series, CD19 CAR T-cell transfer appeared to be feasible, safe, and efficacious in three different autoimmune diseases, providing rationale for further controlled clinical trials. (Funded by Deutsche Forschungsgemeinschaft and others.).
EVALuna2:555903

CD19-targeted CAR T cells in refractory antisynthetase syndrome - Müller, Fabian; Böltz, Sebastian; Knitza, Johannes; Aigner, Michael; Völkl, Simon; Kharboutli, Soraya; Reimann, Hannah; Taubmann, Jule; Kretschmann, Sascha; Rösler, Wolf; Manger, Bernhard; Wacker, Jochen; et al. (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-24

Cellular and humoral immune responses to SARS-CoV-2 vaccination in patients after CD19.CAR T-cell therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Jacobs, Benedikt; Eisenhauer, Nina; Kämpf, Alina; Rösler, Wolf; Kharboutli, Soraya; Mougiakakos, Dimitrios; Lang, Vanessa; et al. (Blood Advances, 2023)
EVALuna2:512817

Identification and characterization of T-cell receptors with therapeutic potential showing conserved specificity against all SARS-CoV 2 strains - Reimann, Hannah; Moosmann, Carolin; Schober, Kilian; Lang, Vanessa; Verhagen, Johan; Zeun, Julia; Mackensen, Andreas; Kremer, Anita; Völkl, Simon; Aigner, Michael (Immunobiology, 2023)
Introduction: Treatment of severe COVID-19 disease can be challenging in immunocompromized patients due to newly emerging virus variants of concern (VOC) escaping the humoral response. Thus, T cells recognizing to date unmutated epitopes are not only relevant for patients’ immune responses against VOC, but might also serve as a therapeutic option for patients with severe COVID-19 disease in the future, e.g. following allogenic stem cell transplantation. Methods: To this purpose, the activation, cytokine profile and specificity of T-cell clones against unmutated and omicron Spike (S)-protein was analyzed, HLA restriction was determined and most promising T-cell receptor (TCR) was introduced into allogeneic T cells via CRISPR/Cas9-mediated orthotopic TCR replacement. Finally, T-cell responses of engineered T cells was determined and durability of the TCR replacement measured. Perspective: SARS-CoV-2 specific engineered T cells recognizing a genomically stable region of the S-protein of all SARS-CoV 2 variants were successfully generated. Such transgenic T cells exhibit favorable effector functions and provide a treatment option of immunocompromised COVID-19 patients.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Orthotopic TCR replacement; SARS-CoV-2; T-cell engineering; T-cell therapy

Identification and validation of expressed HLA-binding breast cancer neoepitopes for potential use in individualized cancer therapy - Reimann, Hannah; Nguyen, Andrew; Sanborn, J. Zachary; Vaske, Charles J.; Benz, Stephen C.; Niazi, Kayvan; Rabizadeh, Shahrooz; Spilman, Patricia; Mackensen, Andreas; Rübner, Matthias; Hein, Alexander; Beckmann, Matthias; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Therapeutic regimens designed to augment the immunological response of a patient with breast cancer (BC) to tumor tissue are critically informed by tumor mutational burden and the antigenicity of expressed neoepitopes. Herein we describe a neoepitope and cognate neoepitope-reactive T-cell identification and validation program that supports the development of next-generation immunotherapies. Methods Using GPS Cancer, NantOmics research, and The Cancer Genome Atlas databases, we developed a novel bioinformatic-based approach which assesses mutational load, neoepitope expression, human leukocyte antigen (HLA)-binding prediction, and in vitro confirmation of T-cell recognition to preferentially identify targetable neoepitopes. This program was validated by application to a BC cell line and confirmed using tumor biopsies from two patients with BC enrolled in the Tumor-Infiltrating Lymphocytes and Genomics (TILGen) study. Results The antigenicity and HLA-A2 restriction of the BC cell line predicted neoepitopes were determined by reactivity of T cells from HLA-A2-expressing healthy donors. For the TILGen subjects, tumor-infiltrating lymphocytes (TILs) recognized the predicted neoepitopes both as peptides and on retroviral expression in HLA-matched Epstein-Barr virus-lymphoblastoid cell line and BC cell line MCF-7 cells; PCR clonotyping revealed the presence of T cells in the periphery with T-cell receptors for the predicted neoepitopes. These high-avidity immune responses were polyclonal, mutation-specific and restricted to either HLA class I or II. Interestingly, we observed the persistence and expansion of polyclonal T-cell responses following neoadjuvant chemotherapy. Conclusions We demonstrate our neoepitope prediction program allows for the successful identification of neoepitopes targeted by TILs in patients with BC, providing a means to identify tumor-specific immunogenic targets for individualized treatment, including vaccines or adoptively transferred cellular therapies.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Antigens; Breast neoplasms; Neoplasm

Influence of DM-sensitivity on immunogenicity of MHC class II restricted antigens - Bernhardt, Anna Luise; Zeun, Julia; Marecek, Miriam; Reimann, Hannah; Kretschmann, Sascha; Bausenwein, Judith; van der Meijden, Edith; Karg, Margarete; Haug, Tabea; Meintker, Lisa; Lutzny-Geier, Gloria; Mackensen, Andreas; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background Graft-versus-host-disease (GvHD) is a major problem in allogeneic stem cell transplantation. We previously described two types of endogenous human leukocyte antigen (HLA)-II restricted antigens depending on their behavior towards HLA-DM. While DM-resistant antigens are presented in the presence of HLA-DM, DM-sensitive antigens rely on the expression of HLA-DO-the natural inhibitor of HLA-DM. Since expression of HLA-DO is not upregulated by inflammatory cytokines, DM-sensitive antigens cannot be presented on non-hematopoietic tissues even under inflammatory conditions. Therefore, usage of CD4+ T cells directed against DM-sensitive antigens might allow induction of graft-versus-leukemia effect without GvHD. As DM-sensitivity is likely linked to low affinity peptides, it remains elusive whether DM-sensitive antigens are inferior in their immunogenicity. Methods We created an in vivo system using a DM-sensitive and a DM-resistant variant of the same antigen. First, we generated murine cell lines overexpressing either H2-M or H2-O (murine HLA-DM and HLA-DO) to assign the two model antigens ovalbumin (OVA) and DBY to their category. Further, we introduced mutations within the two T-cell epitopes and tested the effect on DM-sensitivity or DM-resistance. Furthermore, we vaccinated C57BL/6 mice with either variant of the epitope and measured expansion and reactivity of OVA-specific and DBY-specific CD4+ T cells. Results By testing T-cell recognition of OVA and DBY on a murine B-cell line overexpressing H2-M and H2-O, respectively, we showed that OVA leads to a stronger T-cell activation in the presence of H2-O demonstrating its DM-sensitivity. In contrast, the DBY epitope does not rely on H2-O for T-cell activation indicating DM-resistance. By introducing mutations within the T-cell epitopes we could generate one further DM-sensitive variant of OVA and two DM-resistant counterparts. Likewise, we designed DM-resistant and DM-sensitive variants of DBY. On vaccination of C57BL/6 mice with either epitope variant we measured comparable expansion and reactivity of OVA-specific and DBY-specific T-cells both in vivo and ex vivo. By generating T-cell lines and clones of healthy human donors we showed that DM-sensitive antigens are targeted by the natural T-cell repertoire. Conclusion We successfully generated DM-sensitive and DM-resistant variants for two model antigens. Thereby, we demonstrated that DM-sensitive antigens are not inferior to their DM-resistant counterpart and are therefore interesting tools for immunotherapy after allogeneic stem cell transplantation.
CRIS-Team Scopus Importer:2021-07-30
Keywords: adoptive; antigen presentation; antigens; CD4-positive T-lymphocytes; immunotherapy

Sars-Cov-2 Vaccine-Induced Cellular and Humoral Immunity in Patients after CD19.CAR-T Cell Therapy - Reimann, Hannah; Kremer, Anita; Blumenberg, Viktoria; Schmidt, Katja; Aigner, Michael; Kremer, Andreas; Tenbusch, Matthias; Bruns, Heiko; Harrer, Thomas; Schett, Georg; Müller, Fabian; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Successful Generation of CD19 Chimeric Antigen Receptor T Cells from Patients with Advanced Systemic Lupus Erythematosus - Kretschmann, S.; Völkl, Simon; Reimann, Hannah; Krönke, Gerhard; Schett, Georg; Achenbach, Susanne; Lutzny-Geier, Gloria; Müller, Fabian; Mougiakakos, Dimitrios; Dingfelder, Janin; Flamann, Cindy; Hanssens, L.; et al. (Transplantation and Cellular Therapy, 2022)
Although it has been shown that the production of functional chimeric antigen receptor T cells is feasible in patients with B-cell malignancies, it is currently unclear whether sufficient amounts of functional autologous CAR T cells can be generated from patients with autoimmune diseases. Intrinsic T-cell abnormalities and T-cell–targeted immune suppression in patients with autoimmunity may hamper the retrieval of sufficient T cells and their transduction and expansion into CAR T cells. Patients with active systemic lupus erythematosus (SLE) underwent leukapheresis after tapering glucocorticoids and stopping T-cell–suppressive drugs. This material was used as source for manufacturing anti-CD19 CAR T-cell products (CAR) in clinical scale. Cells were transduced with a lentiviral anti-CD19 CAR vector and expanded under good manufacturing practice (GMP) conditions using a closed, semi-automatic system. Functionality of these CAR T cells derived from autoimmune patient cells was tested in vitro. Six SLE patients were analyzed. Leukapheresis could be successfully performed in all patients yielding sufficient T-cell numbers for clinical scale CAR T-cell production. In addition, CAR T cells showed high expansion rates and viability, leading to CAR T cells in sufficient doses and quality for clinical use. CAR T cells from all patients showed specific cytotoxicity against CD19+ cell lines in vitro. GMP grade generation of CD19 CAR T-cell products suitable for clinical use is feasible in patients with autoimmune disease.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Chimeric antigen receptor; Systemic lupus erythematosus; T cells

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Treatment of a patient with severe systemic sclerosis (SSc) using CD19-targeted CAR T cells. - Bergmann, Christina; Müller, Fabian; Distler, Jörg; Györfi, Andrea Hermina; Völkl, Simon; Aigner, Michael; Kretschmann, Sascha; Reimann, Hannah; Harrer, Thomas; Bayerl, Nadine; Böltz, Sebastian; Wirsching, Andreas; et al. (Annals of the Rheumatic Diseases, 2023)
EVALuna2:537682